Deep Neuromuscular Block Improves Surgical Conditions during Bariatric Surgery and Reduces Postoperative Pain: A Randomized Double Blind Controlled Trial - Torensma, Bart; Martini, Chris H.; Boon, Martijn; Olofsen, Erik; in ‘t Veld, Bas; Liem, Ronald S. L.; Knook, Mireille T. T.; Swank, Dingeman J.; Dahan, Albert (PloS one, 2016)
It remains unknown whether the administration of a deep neuromuscular block (NMB) during bariatric surgery improves surgical conditions and patient outcome. The authors studied the effect of deep versus moderate NMB in laparoscopic bariatric surgery on surgical conditions and postoperative pain. One hundred patients scheduled to undergo elective bariatric surgery were randomized to a deep NMB (post-tetanic-count 2-3) or a moderate NMB (train-of-four 1-2). The quality of the surgical field was scored using the Leiden-Surgical Rating Scale (L-SRS), a 5-point scale ranging from 1 (extremely poor conditions) to 5 (optimal conditions). Three surgeons scored the L-SRS at 10-min intervals during surgery; postoperative pain scores were obtained in the postanesthesia-care-unit (PACU) and on the ward. Mean (95% confidence interval) L-SRS scores in moderate NMB 4.2 (4.0-4.4) versus 4.8 (4.7-4.9) in deep NMB (p < 0.001). Moderate NMB resulted in 17% of scores at L-SRS scores of 1-3, while deep NMB resulted in 100% scores at the high end of the L-SRS (4-5). Deep NMB led to improved pain scores in the PACU (4.6 (4.2-4.9) versus 3.9 (3.6-4.4), p = 0.03) and reduced shoulder pain on the ward (1.8 (1.5-2.1) versus 1.3 (1.1-1.5), p = 0.03). A composite score of pain and opioid use in the PACU favoured deep NMB (p = 0.001). In bariatric surgery, deep relaxation has advantages for surgeon and patient. Compared to moderate NMB, deep NMB produced stable and improved surgical conditions with less postoperative pain.